Mapeamento das normas brasileiras sobre a Inteligência Artificial aplicada ao Direito: uma análise à luz dos direitos fundamentais: Mapping Brazilian rules on Artificial Intelligence applied to Law: an analysis in the context of fundamental rights - Alexandrino de Souza Gomes, Natascha (2024)
With the growing application of Artificial Intelligence (AI) in Law, this article aims to map the current and pending rules in Brazil related to the application of artificial intelligence in the legal field and investigate how such rules are aligned with fundamental rights. Although artificial intelligence can bring advances to the Law, it also presents risks: issues such as privacy, transparency, digital exclusion and the guarantee of non-discrimination were identified as sensitive points. The study reveals that Brazil has a normative framework under development to regulate the application of artificial intelligence in Law. However, it is essential that these rules are constantly reviewed and updated, in order to guarantee the protection and safeguard of rights. Still, there is a need for an approach that aims to ensure that artificial intelligence is used ethically and responsibly by legal practitioners. KEYWORDS: ARTIFICIAL INTELLIGENCE; LAW; LEGAL REGULATION; MAPPING; FUNDAMENTAL RIGHTS.